Co-crystallization of red emitting (NH4)3Sc(SO4)3:Eu3+ microfibers: structure–luminescence relationship for promising application in optical thermometry. Issue 26 (21st June 2022) - Pasechnik, Liliya A.; Peshehonova, Alena O.; Lipina, Olga A.; Medyankina, Irina S.; Enyashin, Andrey N.; Chufarov, Alexander Yu.; Tyutyunnik, Alexander P.
Abstract : Eu-doped (NH4 )3 Sc(SO4 )3 microfibers may become a prominent phosphor for highly sensitive luminescent thermometry in the range 313–373 K. Abstract : The (NH4 )3 Sc(SO4 )3 :0.005Eu 3+ phosphor has been synthesized as rod-like microparticles by crystallization from an aqueous solution. Its crystal structure belongs to the monoclinic system, space group P 21 / c, Z = 4. An enantiotropic first-order phase transition from monoclinic to high-temperature rhombohedral structure (space group R 3 c ) occurs at 350–355 K and compound decomposition begins only above 573 K. Under 248 nm excitation, the compound exhibits luminescence corresponding to the characteristic 5 D0 → 7 F2 transitions in Eu 3+ ions. The absence of an inversion center in the sites occupied by Eu 3+ causes a high intensity of spectral lines at 602–642 nm associated with hypersensitive induced electric dipole 5 D0 → 7 F2 transitions. Heating of the (NH4 )3 Sc(SO4 )3 :0.005Eu 3+ sample to a temperature of 393 K is accompanied by considerable distortion of the Eu 3+ coordination by the phase transition, manifesting a gradual increase in the asymmetry ratio ( R ) between the integral intensities of the lines at 602–642 nm ( 5 D0 → 7 F2 transition) and at 581–602 nm ( 5 D0 → 7 F1 ). When the heating is suppressed, the R level returns to the original value, confirming the reversibility of the structural transformation. A good reproducibility of the obtained R values has been revealed during 4-fold thermal cycling.